If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-6x + 8) = 16 Reorder the terms: -4(8 + -6x) = 16 (8 * -4 + -6x * -4) = 16 (-32 + 24x) = 16 Solving -32 + 24x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 24x = 16 + 32 Combine like terms: -32 + 32 = 0 0 + 24x = 16 + 32 24x = 16 + 32 Combine like terms: 16 + 32 = 48 24x = 48 Divide each side by '24'. x = 2 Simplifying x = 2
| y=(-9)-2x | | -5(4t-3)+9t=2t-8 | | 12x-(9x-5)=17 | | 2(x-2)=5(x+3) | | 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 | | 6x-27=4x+12 | | cx+5=dx-3 |